The predictive value of bedside ultrasound to restore spontaneous circulation in patients with pulseless electrical activity: A systematic review and meta-analysis. - Chunshuang Wu; Zhongjun Zheng; Libing Jiang; Yuzhi Gao; Jiefeng Xu; Xiaohong Jin; Qijiang Chen; Mao Zhang (PLoS ONE)
Background The prognosis of pulseless electrical activity is dismal. However, it is still challengable to decide when to terminate or continue resuscitation efforts. The aim of this study was to determine whether the use of bedside ultrasound (US) could predict the restoration of spontaneous circulation (ROSC) in patients with pulseless electrical activity (PEA) through the identification of cardiac activity. Methods This was a systematic review and meta-analysis of studies that used US to predict ROSC. A search of electronic databases (Cochrane Central, MEDLINE, EMBASE) was conducted up to June 2017, and the assessment of study quality was performed with the Newcastle-Ottawa Scale. Statistical analysis was performed with Review Manager 5.3 and Stata 12. Results Eleven studies that enrolled a total of 777 PEA patients were included. A total of 230 patients experienced ROSC. Of these, 188 had sonographically identified cardiac activity (pseudo-PEA). A meta-analysis showed that PEA patients with cardiac activity on US were more likely to obtain ROSC compared to those with cardiac standstill: risk ratio (RR) = 4.35 (95% confidence interval [CI], 2.20-8.63; p<0,00001) with significant statistical heterogeneity (I2 = 60%). Subgroup analyses were conducted: US evaluation using only on the subxiphoid view: RR = 1.99 (95% CI, 0.79-5.02; p = 0.15); evaluation using various views: RR = 4.09 (95% CI,2.70-6.02; p<0.00001). Conclusions In cardiac arrest patients who present with PEA, bedside US has an important role in predicting ROSC. The presence of cardiac activity in PEA patients may encourage more aggressive resuscitation.